The Future of Health Economics: The Potential of Behavioral and Experimental Economics - Fredrik Hansen; Anders Anell; Ulf-G. Gerdtham; Carl Hampus Lyttkens (Lund University, School of Economics and Management, Department of Economics, 2013)
The health care systems in the Nordic countries are facing key challenges. While the possibilities and willingness to expand health care resources are limited, the demand for health care are increasing due to continuous development of new medical technologies, changing demographics, increasing income level and greater expectations from patients. Consequently, health care organizations are increasingly required to take economic restrictions into account and there is an urgent need to improve the efficiency in the health care sector. A reasonable question to ask is if health economics of today is prepared and equipped to support in meeting these challenges. This article argues that behavioral and experimental economics are promising fields to consider when closing vital knowledge gaps. The aim of this paper is two-fold: introduce the fields of behavioral and experimental economics, and thereafter identify and characterize health economic issues where these two fields have a particularly promising application potential. We also address the advantages of applying a pluralistic view on health economics. Based on the analysis in this, and similar articles, on the development of health economics, we anticipate a dynamic future of health economics.
Keywords: B40; C90; D03; I10; 330; Health economics; Behavioral economics; Experimental economics; Pluralism